Green marketing for brand credibility: The impact of green lifestyle branding among Malaysians - Purnimal, Jayabalakumar (2023)
The aim of this study is to ascertain of the impact that green marketing and its brand credibility has on the green lifestyle among Malaysians. This study also aims to investigate the relationship between brand credibility, trustworthiness, brand loyalty, and expertise when it comes to green lifestyle. This does not only focus on the adaptation and impact that green lifestyle among Malaysians but also on how credible green marketing campaign and what are consumers perceptions towards it. The dimension that this study looked into green marketing are those green branding, ecofriendly products, green advertising, and green labeling on the packaging. A survey research method has been used for this study, where questionnaire has been adapted and adopted from previous related research. The distribution of questionnaire was done via Google Form and data that was collected was analyzed using Statistical Package of Social Science (SPSS) to measure the correlations, regression, and validity of the variables with the hypothesis and conceptual framework model developed. Focusing on the outcome from this study that was conducted, it was noted that consumers have the concern when it comes to the environment and the issues related to it, however they seem to possess enough knowledge in identifying the labels, the usage, and seems to be familiar and experienced with these green eco-friendly products. The expertise level of customer is higher compared to the brand loyalty, brand credibility, or even trustworthiness towards the brand itself. The knowledge that consumer has towards environmental related does not help in making decision together between relationship of green marketing and green lifestyle or green purchasing behavior, while the green consumption is the factor that determines the relationship of green marketing and green lifestyle adaptation, or the impact of green lifestyle. This study brings in the marketing knowledge under the buying practices and behavior that influences the lifestyle. The knowledge of product leads to buying behavior formation where together it incorporates lifestyle practices.